Polymerization of 4-Methylpentene- 1-by Using the MgCl2|Eb|TiCl4|Al(iBu)3 Catalyst System 2. Active Centre Determination - M. A. Abu-Eid; P. J. Tait (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
In the polymerization of 4-methylpentene- 1- by using the MgC12 IEB I TiCL4 IA1(iBu)3 catalyst systems, the effect of catalyst composition on the number of active centres, propagation rate constant, rates of transfer and rate constants for transfer with respect to adsorbed aluminum alkyl and monomer have been reported. The role of aluminum alkyl on the rate of polymerization and the effect of ethyl benzoate on the number of active centres and rate of transfer with respect to aluminum alkyl have been discussed.